Realistic Audio in Immersive Video Conferencing - Mehrotra, Sanjeev; Chen, Wei-ge; Zhang, Zhengyou; Chou, Philip A. (Int'l Conf. on Multimedia and Expo (ICME), 2011)
With increasing computation power, network bandwidth, and improvements in display and capture technologies, fully immersive conferencing and tele-immersion is becoming ever closer to reality. Outside of video, one of the key components needed is high quality spatialized audio. This paper presents an implementation of a relatively low complexity, simple solution which allows realistic audio spatialization of arbitrary positions in a 3D video conference. When combined with pose tracking, it also allows the audio to change relative to which position on the screen the viewer is looking at.